Pembuatan Mainan Edukasi Berbentuk Kincir Angin dari Barang Bekas untuk Meningkatkan Literatur Anak - Maryuni, Maryuni; Nurizzati, Nurizzati (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractBased on the discussion, the following things were concluded. First, the steps of making windmill-shaped educational toys from used goods, namely: (1) collecting tools and materials, (2) cutting the patterned boxes, (3) installing two poles / posts for connecting devices, (4) Making a round pattern, (5) making a propeller pattern, (6) cutting the propeller pattern, (7) sticking straight wood on two poles / bollards. (8) inserting windmill propellers on straight wood, (9) simple windmills have been completed, (10) cutting out fruit poster pictures, (11) glue drawing of fruits on windmill propellers, (12) fruits have been pasted, (13) cutting cardboard pieces, (14) making pieces of cardboard at the pointed ends, (15) placing pieces of cardboard on the edges of the sides of the rectangle, (16) the windmill fence has been finished, (17) installing close the bottle of tea, (18) the windmill has been finished, (19) the windmill is ready to be used by children to play and learn. Secondly, the stage of using windmill educational toys from used goods, namely: (1) preparing tools and materials, (2) making windmills, (3) using windmills by children. Third, the function of educational toys in the form of windmills from used goods, namely: (1) Creating a situation of learning (playing) for children, (2) Growing self-confidence and shaping a positive self-image of children (3) Developing patterns of socialization and emotion of children.Keywords: educational toys, windmills, children